2020
DOI: 10.5194/acp-20-8989-2020
|View full text |Cite
|
Sign up to set email alerts
|

Differences in tropical high clouds among reanalyses: origins and radiative impacts

Abstract: Abstract. We examine differences among reanalysis high-cloud products in the tropics, assess the impacts of these differences on radiation budgets at the top of the atmosphere and within the tropical upper troposphere and lower stratosphere (UTLS), and discuss their possible origins in the context of the reanalysis models. We focus on the ERA5 (fifth-generation European Centre for Medium-range Weather Forecasts – ECMWF – reanalysis), ERA-Interim (ECMWF Interim Reanalysis), JRA-55 (Japanese 55-year Reanalysis),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 132 publications
4
33
0
Order By: Relevance
“…OLR in ERA5 is taken as the negative of the net top-of-atmosphere (TOA) thermal radiation. Wang et al (2017), Tall et al (2019), Wright et al (2020) and Hersbach et al (2020) assessed radiative fluxes in different products and found that ERA5 shows TOA fluxes (including OLR) that are very consistent with the observed. Using observed OLR data such as the daily interpolated data from the NOAA (Liebmann and Smith 1996) does not significantly alter the results obtained with ERA5 (not shown), making it suitable for the present study.…”
Section: Datamentioning
confidence: 63%
“…OLR in ERA5 is taken as the negative of the net top-of-atmosphere (TOA) thermal radiation. Wang et al (2017), Tall et al (2019), Wright et al (2020) and Hersbach et al (2020) assessed radiative fluxes in different products and found that ERA5 shows TOA fluxes (including OLR) that are very consistent with the observed. Using observed OLR data such as the daily interpolated data from the NOAA (Liebmann and Smith 1996) does not significantly alter the results obtained with ERA5 (not shown), making it suitable for the present study.…”
Section: Datamentioning
confidence: 63%
“…It is interesting and important to compare the obtained statistical characteristics of the LWP land-sea gradient with the data provided by reanalyses. Wright et al (2020) note that, though cloud fields in reanalyses are essentially model products, many variables, which influence the cloud fields, are altered during the assimilation process. Therefore, detecting differences between the LWP gradient values obtained in experiments and provided by reanalyses can be valuable for identification of possible problems in reanalyses and for future model development.…”
Section: Comparison With the Reanalysis Datamentioning
confidence: 99%
“…Furthermore, Gleixner et al (2020) showed that in ERA5, near-surface temperatures are less climatologically biased, and their interannual variability better represented than in ERA-Interim across Africa, including in the Sahel band. Similarly, Wang et al (2017), Tall et al (2019), Wright et al (2020) and Hersbach et al (2020) proved that ERA5 represents relatively well the observed OLR over the tropical domain, confirming its suitability as reference dataset for the analysis of tropical modes. The Berkeley Earth Surface Temperatures (BEST; Muller et al 2014;Rohde et al 2016) dataset is used as a second reference dataset to provide an independent evaluation of thermal indices (given that ERA5 is created using the same model as ENS-ext).…”
Section: Description Of the Ecmwf Ens Extended-range Forecasting Systemmentioning
confidence: 63%